Knowing what we can do: actions, intentions, and the construction of phenomenal experience. - Ward, Dave; Roberts, Tom; Clark, Andy (Synthese, 2011)
How do questions concerning consciousness and phenomenal experience relate to, or interface with, questions concerning plans, knowledge and intentions? At least in the case of visual experience the relation, we shall argue, is tight. Visual perceptual experience, we shall argue, is fixed by an agent's direct unmediated knowledge concerning her poise (or apparent poise) over a currently enabled action space. An action space, in this specific sense, is to be understood not as a fine-grained matrix of possibilities for bodily movement, but as a matrix of possibilities for pursuing and accomplishing one's intentional actions, goals and projects. If this is correct, the links between planning, intention and perceptual experience are tight, while (contrary to some recent accounts invoking the notion of 'sensorimotor expectations') the links between embodied activity and perceptual experience, though real, are indirect. What matters is not bodily activity itself, but our practical knowledge (which need not be verbalized or in any way explicit) of our own possibilities for action. Such knowledge, selected, shaped and filtered by the grid of plans, goals, and intentions, plays, we argue, a constitutive role in explaining the content and character of visual perceptual experience.